The importance of low-risk HPV infection for the risk of abnormal cervical cytology/histology in more than 40 000 Danish women. Issue 8 (6th July 2012) - Nielsen, Ann; Iftner, Thomas; Nørgaard, Mia; Munk, Christian; Junge, Jette; Kjaer, Susanne Krüger
Abstract : Objectives: To estimate the age and type-specific distribution of low-risk (LR) human papillomavirus (HPV) types in cervical samples from women in the general population and to assess the distribution of LR-HPV without the coexistence of high-risk HPV types in different cytology and histology categories. Methods: In a cross-sectional study, liquid-based cytology samples (SurePath) were collected over a 3-year period. The samples were HPV tested by Hybrid Capture II (HC2; Digene) and genotyped using a PCR-based assay (INNO-LiPAv2; Innogenetics Inc.). A total of 40 382 women (14–95 years of age) were included in the study. By linkage with the nationwide Pathology Data Bank, the HPV test results were directly linked to cytological diagnoses made from the same samples and to subsequent histology results. Results: Overall, 2790 women (6.9%) tested positive for LR-HPV types, with HPV6 and HPV70 being the most frequent types detected, whereas HPV11 was uncommon. The highest prevalence was observed in the youngest age group (≤19 years). The LR-HPV prevalence was 6.3% in women with normal cytology, 33.1% in atypical squamous cells of undetermined significance (ASCUS), 19.6% in low-grade squamous intraepithelial lesion and 12.7% in those with high-grade squamous intraepithelial lesion. When considering women with LR-HPV alone, the prevalence was 2.0% (normal cytology), 11.3% (ASCUS), 2.6% (low-grade squamous intraepithelial lesion) and 0.7% in women with high-grade squamous intraepithelial lesion, respectively. A similar pattern was observed in relation to the histological diagnoses with the majority of LR-HPV infections detected in CIN1 lesions (24.7%). Conclusions: LR-HPV types alone are relatively common in ASCUS, whereas LR-HPV types without coexisting high-risk HPV types are virtually never detected in severe cervical lesions.